Estimation of Lewis‐negative alleles by high‐resolution melting analysis of three tag SNPs of FUT3 - Soejima, Mikiko; Koda, Yoshiro (Vox sanguinis, 2022)
Background and Objectives The expression of type 1 chain Lewis blood group antigens is regulated by secretor‐type α(1,2)fucosyltransferase, encoded by FUT2, and Lewis α(1,3/1,4)fucosyltransferase, encoded by FUT3. Accumulating evidence has linked Lewis phenotypes or genotypes to various clinical conditions. Thus, in addition to FUT2, large‐scale FUT3 genotyping is important. Because FUT3 has two paralogous genes (FUT5 and FUT6) with high DNA sequence similarity, we should select the polymerase chain reaction (PCR) primers carefully for FUT3 genotyping. Previously, we suggested that 13G>A (rs28362458), 59T>G (rs28362459) and 202T>C (rs812936) could be selected as tag single nucleotide polymorphisms (SNPs) for detection of Lewis‐negative alleles (le). Materials and Methods In this study, three high‐resolution melting (HRM) analyses for genotyping these SNPs were developed and applied for 140 Japanese, eight Ghanaians and four Sinhalese subjects. Results Each of three genotypes of 13G>A (G/G, G/A, A/A), 59T>G (T/T, T/G, G/G) and 202T>C (T/T, T/C, C/C) was discriminated clearly. Although we need to be careful in interpretation of results due to SNPs other than the 59T>G in the amplicon, the results of 59T>G genotyping were in full agreement with the results by a previous PCR‐restriction fragment length polymorphism analysis in 140 Japanese. In addition, three heterozygotes of 202C substitution were identified, and no one having a 13A substitution was found in 140 Japanese. Conclusion The present HRM analyses are useful and reliable methods for large‐scale estimation of le alleles.